Development of online learning video for speaking course as Unila Vclass content - Doni Andra; Rafista Deviyanti; Bayu Saputra (Lighthouse Publishing, 2022)
Technological advances in the 21st century in the industrial 4.0 era are developing very quickly, thereby changing the perspective and mindset of humans in using information technology where the use of information technology has entered the realm of education. In the realm of education, the use of information and communication technology is triggered by learning with the lecture method which is no longer suitable for the learning process. So that innovation is needed in terms of learning media with the use of information and communication technology. One of the learning media that can be developed and used is video learning. This study aims to determine the level of attractiveness and describe the validity of the video learning media in accordance with the competencies that can be used in speaking material. The research method used is R&D with ADDIE research and development design adapted from Lee and Owens (2014). The results showed the validity of the instructional video media based on the results of expert and student assessments. From the expert's assessment got valid results and from students through small groups obtained 88.5% results and from large groups obtained 91.10% results so that they got very valid results. It can be interpreted that the student's response to the learning video is very good.